2021
DOI: 10.3390/vetsci8110257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polymorphisms of the CSN2 Gene Encoding β-Casein in Greek Local Breeds of Cattle

Abstract: This e research focused on the detection and identification of genetic polymorphisms in exon 7 of the β-casein CSN2 gene in blood samples from Greek Holstein cows and from local breeds of cattle, such as Vrachykeratiki, Katerinis, and Sykias. For this purpose, DNA was isolated from 780 blood samples obtained from Greek Holstein cows, 86 from three local breeds of cattle, namely Brachyceros, Katerinis, and Sykias, and 14 from Greek buffalo. The desired region of exon 7 was amplified by PCR, resulting in 121 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
6
2
2
Order By: Relevance
“…Our data were compared with other published data based on group-based genotypes, considering that the B, C, F, and G variants are the A1 group and the A3, D, E, H1, H2, and I variants are the A2 group ( Table 4 ). The frequency of the A2 allele (0.816) in this study was numerically higher than those reported for Holsteins (0.508–0.744) [ 3 , 7 , 8 , 9 , 11 , 12 , 13 ], crossbreeds (0.568–0.606) [ 14 , 15 , 16 ], Mexican Jerseys (0.738) [ 10 ], and Danish Jerseys (0.700) [ 8 ]. If the herd aims to produce milk only from the A2 variant (A2 milk), a high frequency of the A2 allele is favored for selected breeding.…”
Section: Resultscontrasting
confidence: 74%
“…Our data were compared with other published data based on group-based genotypes, considering that the B, C, F, and G variants are the A1 group and the A3, D, E, H1, H2, and I variants are the A2 group ( Table 4 ). The frequency of the A2 allele (0.816) in this study was numerically higher than those reported for Holsteins (0.508–0.744) [ 3 , 7 , 8 , 9 , 11 , 12 , 13 ], crossbreeds (0.568–0.606) [ 14 , 15 , 16 ], Mexican Jerseys (0.738) [ 10 ], and Danish Jerseys (0.700) [ 8 ]. If the herd aims to produce milk only from the A2 variant (A2 milk), a high frequency of the A2 allele is favored for selected breeding.…”
Section: Resultscontrasting
confidence: 74%
“…В -казеине А2 присутствие пролина вместо гистидина предотвращает гидролиз пептидной связи между 66-м и 67-м аминокислотными остатками и ингибирует выработку -казоморфина-7 (91,92). При последовательном желудочно-кишечном переваривании молока, содержащего β-казеин А1, количество образующегося β-казоморфина-7 в 4 раза выше, чем при переваривании молока, содержащего β-казеин А2 (93)(94)(95).…”
Section: рис 2 первичная последовательность для наиболее распростране...unclassified
“…However, along with such widely known qualitative trait loci as kappa casein, prolactin, beta-lactoglobulin, leptin, etc., related to the expression of productive traits of animals, in a few recent years, there has been a steady interest in the beta-casein gene, the allelic variants of which are related to the parameters of milk quality (Cieślińska et al, 2019;Sebastiani et al, 2022;Jiménez-Montenegro et al, 2022). A 1 and A 2 belong to one of the best-studied and promising allele systems of beta-casein from the standpoint of applied genetics of cattle (Antonopoulos et al, 2021). As shown in numerous studies, various forms of beta-casein are associated with a number of human pathological states which makes the CSN2 gene a relevant research object in the context of the production performance of different dairy cattle breeds (Summer et al, 2020;Bisutti et al, 2022;De Vitte et al, 2022).…”
Section: Introductionmentioning
confidence: 99%